A sequential treatment of intermediate tropical landfill leachate using a sequencing batch reactor (SBR) and coagulation. (1st January 2018) - Yong, Zi Jun; Bashir, Mohammed J.K.; Ng, Choon Aun; Sethupathi, Sumathi; Lim, Jun-Wei
Abstract: The increase in landfill leachate generation is due to the increase of municipal solid waste (MSW) as global development continues. Landfill leachate has constantly been the most challenging issue in MSW management as it contains high amount of organic and inorganic compounds that might cause pollution to water resources. Biologically treated landfill leachate often fails to fulfill the regulatory discharge standards. Thus, to prevent environmental pollution, many landfill leachate treatment plants involve multiple stages treatment process. The Papan Landfill in Perak, Malaysia currently has no proper leachate treatment system. In the current study, sequential treatment via sequencing batch reactor (SBR) followed by coagulation was used to treat chemical oxygen demand (COD), ammoniacal nitrogen (NH3 -N), total suspended solids (TSS), and colour from raw landfill leachate. SBR optimum aeration rate, L/min, optimal pH and dosage (g/L) of Alum for coagulation as a post-treatment were determined. The two-step sequential treatment by SBR followed by coagulation (Alum) achieved a removal efficiency of 84.89%, 94.25%, 91.82% and 85.81% for COD, NH3 -N, TSS and colour, respectively. Moreover, the two-stage treatment process achieved 95.0% 95.0%, 95.3%, 100.0%, 87.2%, 62.9%, 50.0%, 41.3%, 41.2, 34.8, and 22.9 removals of Cadmium, Lead, Copper, Selenium, Barium, Iron, Silver, Nickel, Zinc, Arsenic, and Manganese, respectively. Graphical abstract: Highlights: Landfill leachate contains high amount of non-biodegradable organic compounds and NH3 -N. Biologically treated leachate often fails to satisfy the regulatory discharge standards. Sequential treatment via SBR/coagulation was used to treat raw Municipal landfill leachate. The optimum treatment efficiency was 84.89, 94.25, 91.82 and 85.81% for COD, NH3 -N, TSS and colour.